Possible Drug-Drug Interactions Between Mesalamine and Tricyclic Antidepressants Through CYP2D6 Metabolism – In silico and In vitro Analyses - Ozen, Melek B.; Gazioglu, Isil; Ozgun Acar, Ozden; Guner, Huseyin; Semiz, Gurkan; Sen, Alaattin (Drug Research, 2025)
Mesalamine (mesalazine, 5-aminosalicylic acid, 5-ASA) is an essential anti-inflammatory agent both used for therapy and as a remission control in patients with inflammatory bowel diseases (IBD) such as ulcerative colitis (UC). Tricyclic antidepressants (TCAs) are used to alleviate remaining symptoms in patients already receiving IBD therapy or with quiescent inflammation. The cytochrome P4502D6 enzyme is involved in the metabolism of TCAs. Hence, it is crucial to investigate the role of CYP2D6 in 5-ASA metabolism. Initially, in silico analysis involving the docking of 5-ASA to CYP2D6 and molecular dynamics simulations was conducted. Next, the rate of O-demethylation of a nonfluorescent probe 3-[2-(N,N-diethyl-N-methylammonium)-ethyl]-7-methoxy-4-methylcoumarin (AMMC) into a fluorescent metabolite AMHC (3-[2-(N,N-diethyl-N-methylammonium)ethyl]-7-hydroxy-4-methylcoumarin) was optimized with baculosomes co-expressing human CYP2D6 and human P450 oxidoreductase (hCPR) to monitor CYP2D6 activity in a microtiter plate assay. The apparent Km and Vmax were found to be 1.30 μM and 32.68 pmol/min/mg of protein for the O-demethylation of AMMC to AMHC, and the reaction was linear for 40 min. Then, nonselective inhibition of CYP2D6 activity with various concentrations of 5-ASA was detected. Finally, the conversion of AMMC to metabolites was analyzed by HPLC-ESI-MS/MS spectrometry, and none were identified. Thus, this study suggests that concurrent use of mesalamine with TCA may lead to adverse effects, and CYP2D6 genotyping should be routinely performed on these patients to eliminate possible threats.
Keywords: adverse drug reactions; antipsychotic drugs; drug metabolism; pharmacokinetics